Active Learning Models Type Index Card Match: Improve the Learning Outcomes Students in the Pancasila Education - Oktaviani, Linda; Marzuki; Aulia, Ullu Yandi (Universitas Pendidikan Ganesha, 2024)
The utilization of teacher-centered learning models has been shown to adversely affect students' academic performance. This study aims to analyze the impact of implementing the Index Card Match teaching method on the academic outcomes of eighth-grade students in the subject of Pancasila Education. The research employed an experimental method with a quantitative approach. A sample size of 70 students was selected using nonprobability sampling through purposive sampling techniques. Data collection was carried out via documentation and tests. Hypothesis testing was conducted using simple linear regression analysis. The results of the study indicate a significant impact of the Index Card Match teaching method on the academic performance of eighth-grade students. This is evidenced by the data analysis, which revealed a significance value of 0.000 using simple linear regression. This value signifies that the alternative hypothesis (Ha) is accepted while the null hypothesis (Ho) is rejected, given that the obtained significance value (0.000) is less than 0.05. Therefore, it can be concluded that the implementation of the Index Card Match teaching method has a significant effect on the academic outcomes of eighth-grade students in the subject of Pancasila Education.